2017
DOI: 10.18632/oncotarget.21340
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil/lymphocyte ratio is a more sensitive systemic inflammatory response biomarker than platelet/lymphocyte ratio in the prognosis evaluation of unresectable pancreatic cancer

Abstract: Multiple cancers arise from sites of infection, chronic irritation, and inflammation. It has been widely accepted that pancreatic cancer is an inflammation-driven cancer. In this study, we investigated the application value of systemic inflammatory markers, neutrophil to lymphocyte ratio (NLR) and platelet to lymphocyte ratio (PLR), in the prediction of chemotherapy response and prognosis in patients with late pancreatic cancer. 122 patients with inoperable pancreatic cancers were included and separated into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 47 publications
6
28
0
1
Order By: Relevance
“…However, in subgroup analyses, a high PLR was associated with worse OS only in Asian patients and in those who underwent mixed treatment (surgery plus chemo/radiotherapy). Our meta-analysis demonstrated that NLR is a better predictor of prognosis of patients with PC than PLR, which is also consistent with the results of previous studies [ 35 , 57 ]. Our analysis may provide important information to support treatment decision-making, including pursuing more aggressive treatments.…”
Section: Discussionsupporting
confidence: 92%
“…However, in subgroup analyses, a high PLR was associated with worse OS only in Asian patients and in those who underwent mixed treatment (surgery plus chemo/radiotherapy). Our meta-analysis demonstrated that NLR is a better predictor of prognosis of patients with PC than PLR, which is also consistent with the results of previous studies [ 35 , 57 ]. Our analysis may provide important information to support treatment decision-making, including pursuing more aggressive treatments.…”
Section: Discussionsupporting
confidence: 92%
“…Treatment-associated changes in the T-cell repertoire Several studies have revealed that both local and systemic inflammation have an important role in cancer progression and response to immunotherapy. To assess the patient's ability to mount a systemic inflammatory response or immunological fitness for immunotherapy, we examined the neutrophil-to-lymphocyte ratio (NLR), which has been shown to correlate with patient outcomes in a variety of solid cancers, including PDAC (30)(31)(32). To perform this analysis, we separated patients into long-term survivors (LTS, OS > 6 months) and short-term survivors (STS, OS < 6 months).…”
Section: Antitumor Activity -Intravenously Delivered Pelareorep Replimentioning
confidence: 99%
“…As systemic alteration of inflammation leads to alteration in the peripheral blood leukocytes, NLR can act as a proxy measurement of the degree of inflammation in cancers. [4,5] Similarly, platelets release pro-inflammatory mediators, such as cytokines and chemokines, which exacerbate the inflammatory microenvironment in tumors, making PLR another viable measure of inflammation. [6,7] Monocytes have also been observed to have a key role in inflammation, also having been implicated in many inflammatory diseases, including atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%